Polymeric depressants in purification by flotation of molybdenite - P. Braga; A. Chaves; A. Luz; S. França (International Mineral Processing Congress, 2014)
"In Brazil, there are no official reserves of molybdenum, and the unofficial reserves are modest. Therefore, the molybdenum ore (molybdenite) produced as a co-product or by-product of emerald mining in the region of Campo Formoso, BA, has arisen as the only economic option. The flotation process is commonly used in Brazil for the recovery of molybdenite from emerald mining tailings, but it produces low-content molybdenite concentrates, thereby resulting in a product with low economic value. The molybdenite concentrate produced in Campo Formoso contains 83.5% MoS2 (50% Mo), which is less than the international standard product that contains > 90% MoS2 (54% Mo).This low value is due to the presence of talc, which is a naturally hydrophobic mineral that is also floated with the molybdenite during the flotation process. Separability studies were done in a Partridge-Smith cell using dextrin and quebracho as a molybdenite depressor in solution at different concentrations and pH values to produce a technical-grade concentrate (i.e., 90% MoS2). These basic studies were accompanied by measurements of the zeta potential and contact angle, which was determined by the capillary rise method. The results of these floatability studies were used in bench flotation tests, which were performed in a Denver laboratory flotation cell. A molybdenite concentrate of 93.4% MoS2 was obtained when dextrin was used at a concentration of 100 g/t."